2005
DOI: 10.1016/s0002-9440(10)61247-3
|View full text |Cite
|
Sign up to set email alerts
|

Massive Apoptosis in Lymphoid Organs in Animal Models for Primary and Secondary Progressive Multiple Sclerosis

Abstract: The mechanism(s) responsible for generating the different forms of multiple sclerosis, primary progressive (PP) and secondary progressive (SP) versus relapsing-remitting (RR), is not well understood. Using myelin oligodendrocyte glycoprotein (MOG)(92-106), we have established animal models that mimic the different types of multiple sclerosis. A.SW mice develop PP or SP-experimental allergic encephalomyelitis (EAE) with large areas of demyelination and high titers of MOG antibody whereas SJL/J mice develop RR-E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 75 publications
3
45
0
1
Order By: Relevance
“…It is unclear whether this difference resides in the nature of the antigen. MP4 contains the PLP:178-191 determinant and PLP-induced EAE in other mouse strains is indeed characterized by massive chronic demyelination (Tsunoda et al, 2005). The fact that we did not observe demyelination using the isolated PLP:178-191 peptide might be related to this peptide being a cryptic determinant in the B6 mouse.…”
Section: Discussionmentioning
confidence: 63%
“…It is unclear whether this difference resides in the nature of the antigen. MP4 contains the PLP:178-191 determinant and PLP-induced EAE in other mouse strains is indeed characterized by massive chronic demyelination (Tsunoda et al, 2005). The fact that we did not observe demyelination using the isolated PLP:178-191 peptide might be related to this peptide being a cryptic determinant in the B6 mouse.…”
Section: Discussionmentioning
confidence: 63%
“…IL-12 and IFN-γ would then activate autoimmune T helper (Th) 1 cells. In this study, we found that MCMV challenge induced higher anti-PLP IgG2c (formerly IgG2a of Igh-1b allotype) (Jouvin-Marche et al, 1989;Tsunoda et al, 2005aTsunoda et al, ,2005b responses and that the anti-PLP IgG2c/G1 ratio in MCMV challenge was higher than in VV and LCMV challenge. Since Th1 and Th2 cells help with the Ig isotype switch to IgG2a (2c) and IgG1, respectively, our results are consistent with the fact that MCMV infection skews immune responses toward Th1.…”
Section: Discussionmentioning
confidence: 61%
“…There was no statistical difference in PLP antibody titers between VV-challenged mice and naïve mice. We also measured anti-PLP IgG1 and IgG2c (formerly IgG2a of Igh-1b allotype) (Jouvin-Marche et al, 1989;Tsunoda et al, 2005aTsunoda et al, ,2005b. We found that anti-PLP IgG1 and IgG2c titers were low in all mouse groups.…”
Section: Challenge Induces Splenomegaly and Plp Antibody Responsesmentioning
confidence: 88%
See 1 more Smart Citation
“…Culture supernatants were harvested 48 h after stimulation. IFN-␥ and IL-4 were measured using the enzyme-linked immunosorbent assay system OptEIA set (BD PharMingen, San Jose, CA), according to the manufacturer's instructions (44).…”
Section: Animal Experiments Four-week-old Cd1mentioning
confidence: 99%